Pursuing Quality Education in Physical and Rehabilitation Medicine in Japan - Asami, Toyoko (Frontiers in Rehabilitation Sciences, 2022)
A current issue in Japanese medical education is the development of clinical education that is in accordance with the advances being made in medical care. In 2021 a comprehensive system for the coordination of undergraduate practical training and post-graduation clinical training was created, which is contributing to the emergence of a new trend in medical education. In this context, rehabilitation medicine faces a problem: The fact that it has a short history and that it is small in scale means that its position in the education system is weak. On the other hand, rehabilitation education – which is unique in that its focus is on activities – accepts the major demands placed on it by an aging society, and as a result since 2000 there has been a rapid increase in its clinical importance, as indicated by the rapid increase in the number of therapists and an increase in the proportion of total medical costs occupied by rehabilitation medicine to 5%. Therefore, when one considers the issue of postgraduate education that is effective in meeting these needs, one sees that it is necessary to devise more effective links to pre-graduate education. One key to the success of this effort is creating a flexible education system that takes advantage of the merits of small groups while maintaining a sufficient understanding of medical education as a whole – although avoiding being hampered by the system as a whole. Specifically, this effort should promote “inspired motivation” – which is one of the merits of apprenticeship that takes the form of external motivation – while at the same time placing importance on the profession of clinical care, emphasizing rehabilitation medicine’s uniqueness in its focus on activities, and providing young physicians with a practical training community that operates clinical teamwork in a flexible manner. In addition, it should stimulate curiosity, which is a type of internal motivation, while at the same time introduce students to new concepts that provide medicine with the perspective of activities. Naturally, this point must be emphasized within the limited scope of undergraduate education.